2022
DOI: 10.1186/s12906-022-03760-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of qigong exercise on the physical and mental health of college students: a systematic review and Meta-analysis

Abstract: Background Physical and mental health problems are becoming more serious among college students due to lifestyle changes and increased academic stress. Qigong exercise has been regarded as a potentially effective intervention to improve the physical and mental health of college students. Methods Eleven databases were searched from their respective inception dates to April 2022. Relevant randomized controlled trials (RCTs) were included. Physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…According to a broad definition, some traditional Chinese Integrative Body-Mind Training (IBMT) regimens, like Tai Chi, Baduanjin, and Qigong, were also included in the category of MBIs ( Creswell, 2017 ). Research has shown that these exercise regimens can benefit practitioners’ physical and mental health ( Zou et al, 2018 ; Li et al, 2019 ; Gong et al, 2022 ; Lin et al, 2022 ). Researchers should continue to explore what modifications are necessary for these IBMT programmes to be delivered online for university students.…”
Section: Discussionmentioning
confidence: 99%
“…According to a broad definition, some traditional Chinese Integrative Body-Mind Training (IBMT) regimens, like Tai Chi, Baduanjin, and Qigong, were also included in the category of MBIs ( Creswell, 2017 ). Research has shown that these exercise regimens can benefit practitioners’ physical and mental health ( Zou et al, 2018 ; Li et al, 2019 ; Gong et al, 2022 ; Lin et al, 2022 ). Researchers should continue to explore what modifications are necessary for these IBMT programmes to be delivered online for university students.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has consistently identified a significant negative association between the practice of psychological relaxation techniques, such as Qigong ( Lin et al, 2022 ), deep breathing ( Cheng et al, 2019 ), Yoga ( Jonsson et al, 2020 ), Meditation ( Saeed et al, 2019 ), and the occurrence of anxiety and depression. Our study also revealed a similar association between engaging in relaxation techniques and the rates of anxiety and depression among patients with ED.…”
Section: Discussionmentioning
confidence: 99%
“… First-author, year No. of participants Intervention Comparison Mental disorders Outcomes Effect metrics Overall Rating Gong et al., 2023 ( Gong et al., 2023 ) 447/461 MBCT Inactive (waitlist) Depression, anxiety, stress Depression, anxiety, stress SMD Moderate Oliveira Silva et al., 2023 ( Oliveira Silva et al., 2023 ) 609/574 Simulation; compared conventional educational strategies with simulation Conventional educational interventions Stress, anxiety Stress, anxiety SMD High Chandler et al., 2022 ( Chandler et al., 2022 ) 6558/6356 CBT-I-based interventions Waitlist or treatment as usual (passive) Alternative intervention (active) Sleep disturbance, anxiety, depression Sleep, anxiety, depression SMD Low Du et al., 2022 ( Du et al., 2022 ) 369/332 Taijiquan intervention Regular physical activity group Depression, anxiety Depression, anxiety SMD Low Huber et al., 2022 ( Huber et al., 2022 ) 320/312 Active intervention Active animal control Active other control No-treatment control Acute anxiety, acute self-perceived stress, negative affect Acute anxiety, acute self-perceived stress, negative affect SMD High Lin et al., 2022 ( Lin et al., 2022 ) 712/714 Qigong exercise Original sports exercise practices, relaxation training or maintaining the original lifestyle without any intervention Depression, anxiety, mood Depression, ...…”
Section: Resultsmentioning
confidence: 99%